Seleksi Siswa Baru di MAS Bahrul Uluum Al Kamal dengan Profile Matching - Roby Setiawan; Guntur Maha Putra; Sri Rezki Maulina Azmi (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The purpose of this study was to determine the design of a web-based decision support system in the selection of new students at MAS Bahrul Uluum Al Kamal using the PHP programming language and MySQL database, implementing a decision support system in the selection of new students so that the results are more objective to determine new students accepted at MAS. Bahrul Uluum Al Kamal and applying the Profile Matching method with the aim of accelerating the decision-making process in determining new students at MAS Bahrul Uluum Al Kamal. The research method used is quantitative with the calculation of Profile Matching. The criteria used in this study were report cards, online tests, al-qur'an reading tests, non-academic achievements and interview tests. The alternative used in this study is prospective new students who register at MAS Bahrul Uluum Al Kamal. It is hoped that the results of this study are the selection of new students at MAS Bahrul Uluum Al Kamal to be faster, more precise and accurate using the profile matching method which gives the results of the calculation in the form of ranking the highest to the lowest score and the highest score is the result needed for consideration by the MAS Bahrul Uluum Al Kamal when selecting new students.